Dinuclear Complexes Formed by Hydrogen Bonds: Synthesis, Structure and Magnetic and Electrochemical Properties. Issue 29 (2nd May 2017) - Granelli, Matteo; Downward, Alan M.; Huber, Robin; Guénée, Laure; Besnard, Céline; Krämer, Karl W.; Decurtins, Silvio; Liu, Shi‐Xia; Thompson, Laurence K.; Williams, Alan F.
Abstract: The synthesis is reported of a series of homo‐ and hetero‐dinuclear octahedral complexes of the ligand1, 1, 2‐bis(1‐methyl‐benzimidazol‐2‐yl) ethanol, where the two metal centres are linked by hydrogen bonds between coordinated alcohols and coordinated alkoxides. Homonuclear divalent M II M II, mixed‐valent M II M III and heteronuclear M II M′ III species are prepared. The complexes have been characterised by X‐ray crystallography and show unusually short O⋅⋅⋅O distances for the hydrogen bonds. Magnetic measurements show the hydrogen‐bond bridges can lead to ferromagnetic or antiferromagnetic coupling. The electrochemistry of the dinuclear species is significantly different from the mononuclear systems: the latter show irreversible waves in cyclic voltammograms as a result of the need to couple proton and electron transfer. The dinuclear species, in contrast, show reversible waves, which are attributed to rapid intramolecular proton transfer facilitated by the hydrogen‐bonded structure. Abstract : Held together by strong bonds : A route to a series of dinuclear complexes held together by unusually strong hydrogen bonds is presented. The complexes show ferromagnetic or antiferromagnetic coupling through the bridge, and outer‐sphere electron transfer is facilitated by inner‐sphere proton transfer.